Pengaruh Faktor Eksternal dan Internal Terhadap Kinerja Pelaku UMKM Budidaya Rumput Laut di Kota Bontang - Ilham Akbar Amor; Ana Noor Andriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this study was to find out whether there is an influence from internal factor variables and external factors on business performance in seaweed cultivation SMEs in Bontang City. This research is quantitative research with data collection using a questionnaire. The number of respondents used was 30 respondents who were selected using purposive sampling with the criteria of being registered at the office of industry, trade, cooperatives, and SMEs in Bontang City. The testing in this study uses the SPSS output and the data analysis technique used is through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis testing, and hypothesis testing. The results of this study are that internal factor variables have a positive and significant effect on Udsha performance, external factors have no influence on business performance, and internal factor variables and external factors have a positive effect simultaneously on business performance. The r square value obtained where internal and external factors can explain the performance variable as much as 55.2% while 45.8% is explained by other variables.